2018
DOI: 10.1186/s12935-018-0650-8
|View full text |Cite
|
Sign up to set email alerts
|

BORIS: a key regulator of cancer stemness

Abstract: BORIS (CTCFL) is a DNA binding protein which is involved in tumorigenesis. Although, there are different opinions on the level of gene expression and function of BORIS in normal and cancer tissues, the results of many studies have classified BORIS as a protein belonging to cancer/testis (CT) genes, which are identified as a group of genes that are expressed normally in testis, and abnormally in various types of cancers. In testis, BORIS induces the expression of some male germ cell/testis specific genes, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 147 publications
2
36
0
Order By: Relevance
“…becomes aberrantly re-activated in various types of cancer, including melanoma (42). Here we confirm BORIS expression at the mRNA level (36,44) and demonstrate BORIS protein expression in melanoma cell lines.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…becomes aberrantly re-activated in various types of cancer, including melanoma (42). Here we confirm BORIS expression at the mRNA level (36,44) and demonstrate BORIS protein expression in melanoma cell lines.…”
Section: Discussionsupporting
confidence: 75%
“…Our finding that altered BORIS expression leads to large-scale changes in gene expression was expected, as BORIS is known to act as a transcriptional regulator (24,25,29,33). In addition, it reflects the numerous cellular processes that BORIS is involved in (42,53), many of which are altered during carcinogenesis. Multiple studies found that increased BORIS expression is linked to poor prognosis and more advanced stages of disease, hence BORIS being considered an oncogene (54)(55)(56)(57).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…). Evidence shows that these cancer/testis–specific transcripts, instead of aiding nongenetic “noise” during tumorigenesis, support cell‐autonomous behavior and may serve as potential intervention targets …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that its transcriptional activation regulates chromatin accessibility in the early mouse embryo, and it is involved in nuclear organization and cellular identity of embryonic stem cells [43,44]. Thus, the activity of LINE-1 may also be secondary to pluripotency and cancer stemness, where transcription factors and methyltransferases cooperate to establish uncontrolled proliferation ability, enhanced potential to self-renew, migration capacity, and differentiation potential into different cell types [45,46].…”
Section: Discussionmentioning
confidence: 99%